Pendidikan Perempuan di Kawasan Perbatasan dalam Perspektif Sosial Budaya Suku Galela - Irawati Sabban; Nurhani Mahmud (Mahesa Research Center, 2022)
This article aims to determine the socio-cultural perspective of the Galela Tribe towards women's education in border areas. The problem is focused on equal distribution of education for women in Morotai Island Regency as the border area of Indonesia and the Philippines. This study used a qualitative approach, data was collected through in-depth interview and observation techniques. Sources of data in this study were women from the Galela Tribe residing in the village of Sakita, North Morotai District, Mira Village, East District, and Momojiu Village, South Morotai District, selected by purposive sampling. The three villages are the oldest traditional villages in Kab. Morotai Island, which used to be the villages of the Moro Kingdom, until now these villages are traditional villages. The results of the study conclude that it is true that there is a view that women are not important to get education for their lives, but along with the times, women from the Galela tribe have begun to gain access to education even to college.